The Strategic Behavior of Business Leaders with regard to the Daip Professional Integration Assistance Scheme - Case Study: The Wilaya of Bejaia - - Idir KICHER; Mohamed Akil FARADJI (Social Sciences Journal, 1970)
The concept of the professional insertion is well and more complicated than one mightthink. It is an over all complex process. It is true that in Algeria, the work market seems to beexclusively governed by the simple ¨offer and demand¨ policy, but it is actually more complexthan what one might think. It is a network composed of many actors that are: the state, thebusiness leaders and the young graduated students. Within this network, interactions betweenthe actors occur (embeddedness). Each one try to satisfy his needs and reach his goals byusing different and appropriate strategies. In this paper, we will only examine the strategiesdeveloped by the business leaders of the different legal sectors (administrative, privateeconomic and public economic) vis-à-vis the DAIP. Is they will play the game to participatein the reduction of the rate of unemployment in general and particularly that of graduatedstudents by creating stable and lasting jobs?